DAMPAK PENGGUNAAN TEKNOLOGI TERHADAP ANAK TINGKAT ATAS SEKOLAH DASAR - Dewi Rumapea, Vanni Sulastri; Septian Alya Hustria; Fajerina Eka Az-Zahra (STAI Nusantara Banda Aceh, 2025)
The advancement of information technology has profoundly transformed the manner in which children acquire knowledge, engage in recreational activities, and interact within their social environments. Children approaching the culmination of their primary education and who are being raised in the digital age are considerably impacted by the utilization of technological devices, including the internet. This journal intends to explore the ramifications of technology on children, encompassing its effects on their cognitive, social, and emotional development, as well as their physical health. Furthermore, this journal will underscore the importance of the judicious use of technology. Technology has become a fundamental component of contemporary life; however, excessive engagement with technology can yield detrimental effects on children’s development. This abstract will delineate the challenges encountered by children in the present digital era and will also propose practical solutions for parents and educators to assist children in utilizing technology in a manner that is both healthy and productive.